Antimicrobial activity of bacteria isolated from Leptinotarsa decemlineata and Solanum tuberosum - Tatiana A Efimenko; Andrey V Yakushev; Mariia V Demiankova; Alla A Glukhova; Tamara I Khusnetdinova; Vera S Sadykova; Olga V Efremenkova (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
From the intestinal microbiota of Colorado potato beetles and their larvae (Leptinotarsa decemlineata), as well as from their feed - potato leaves, 18 bacteria of different species exhibiting antimicrobial activity (56% of the total number of isolated strains) were isolated. The species of bacteria from all three sources of excretion are different. The following 12 species were described for the first time in the gut microbiota of L. decemlineata larvae and imago: Micromonospora phytophila, Neobacillus drentensis, Pseudomonas gessardii, P. poae, P. rhizosphaerae, Pantoea agglomerans, Streptomyces chartreusis, S. clavifer, S. microflavus, S. rishiriensis, S. badius, and S. coelicoflavus. Antimicrobial activity was not previously known for three species (Staphylococcus argenteus, S. camponoticapitis, S. clavifer). Antimicrobial activity against methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Leuconostoc mesenteroides, multidrug-resistant P. aeruginosa, and Mycobacterium smegmatis was revealed. The gut microbiota of Colorado potato beetles can be considered an encouraging source of antibiotic-producing strains that overcome drug resistance of pathogenic bacteria, as well components of biopesticides.